2006
DOI: 10.1001/archotol.132.6.668
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Events of Disease Progression in Head and Neck Squamous Cell Carcinoma

Abstract: To examine the promoter methylation status of the 22 cancer genes and their contribution to disease progression in 6 head and neck squamous cell carcinoma (HNSCC) cell lines. Design: A panel of 41 gene probes, designed to interrogate 35 unique genes with known associations to cancer including HNSCC, was interrogated for alterations in gene copy number and aberrant methylation status (22 genes) using the methylation-specific multiplex ligationdependent probe amplification assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 38 publications
4
115
2
1
Order By: Relevance
“…Among the high-throughput techniques available for epigenetic alterations assessment, the CpG array represents the major comprehensive platform already applied to identify methylation candidates in bladder cancer. 15 The advantages of the MS-MLPA technique as an alter- native for MS-PCR include allowing screening of more than 25 predefined promoter methylation candidates in one single step using a low amount of DNA (100 to 200 ng), 16 which is feasible using DNA extracted from tissue (even in formalin-fixed material) 18 ; providing semiquantitative data; and requiring only standard laboratory equipment. Furthermore, the (potentially) troublesome bisulfite conversion of unmethylated cytosines required for MS-PCR [31][32][33][34][35][36][37][38][39] can be omitted in MS-MLPA using methylationsensitive digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Among the high-throughput techniques available for epigenetic alterations assessment, the CpG array represents the major comprehensive platform already applied to identify methylation candidates in bladder cancer. 15 The advantages of the MS-MLPA technique as an alter- native for MS-PCR include allowing screening of more than 25 predefined promoter methylation candidates in one single step using a low amount of DNA (100 to 200 ng), 16 which is feasible using DNA extracted from tissue (even in formalin-fixed material) 18 ; providing semiquantitative data; and requiring only standard laboratory equipment. Furthermore, the (potentially) troublesome bisulfite conversion of unmethylated cytosines required for MS-PCR [31][32][33][34][35][36][37][38][39] can be omitted in MS-MLPA using methylationsensitive digestion.…”
Section: Discussionmentioning
confidence: 99%
“…One might therefore suggest that this tumour suppressor requires a critical transcript level to prevent aggressive behaviour of malignant cells in solid tumours resulting in progressive and advanced cancer. Promoter hypermethylation of CADM1 has been observed in many malignancies (Fukami et al, 2003;Li et al, 2005;Ehrlich et al, 2006;Kikuchi et al, 2006;Worsham et al, 2006) and has thus been suggested to represent the most common molecular mechanism responsible for gene silencing of CADM1 in human cancers. In contrast to these reports, we could not detect any associations of CADM1 expression level with the methylation status of the CADM1 promoter region in a set of 18 primary neuroblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of CADM1 expression has been described in many malignancies, including liver, pancreatic, breast, brain and prostate cancers, particularly in those showing invasion or metastasis (Kuramochi et al, 2001;Fukuhara et al, 2002;Jansen et al, 2002;Houshmandi et al, 2006;Heller et al, 2007). Promoter hypermethylation was reported to account for downregulation of CADM1 in several human cancers (Murakami, 2005;Ehrlich et al, 2006;Kikuchi et al, 2006;Worsham et al, 2006). Moreover, high expression levels of CADM1 from a recombinant adenovirus vector were shown to inhibit cell proliferation and to induce apoptosis in the non-small cell lung cancer cell line A549 (Mao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The method has been detailed elsewhere [9][10][11][12][13]. The assay has been used successfully for the detection of deletions and duplications and the characterization of chromosomal aberrations for gains and losses of genes in cell lines and tumor samples [9][10][11][12][13]. Probes added to the samples are amplified and quantified instead of target nucleic acids.…”
Section: The Multiplex Ligation-dependent Probe Amplification Assay (mentioning
confidence: 99%
“…For cell lines, where normal DNA is not available, control (normal) female DNA samples are run with each probe set. Quantification of loss or gain of gene loci is determined through a process of normalization [9][10][11][12][13]. The latter addresses variations in the surface area of a peak (intensity) encountered due to fluctuations in the assay run, such as amount of DNA, ploidy variations, and PCR conditions.…”
Section: The Multiplex Ligation-dependent Probe Amplification Assay (mentioning
confidence: 99%